A systematic study of electron or hole transfer along DNA dimers, trimers and polymers - Simserides, C. (Chemical Physics, 2014)
A systematic study of carrier transfer along DNA dimers, trimers and polymers including poly(dG)-poly(dC), poly(dA)-poly(dT), GCGCGC..., ATATAT... is presented allowing to determine the spatiotemporal evolution of electrons or holes along a N base-pair DNA segment. Physical quantities are defined including maximum transfer percentage p and pure maximum transfer rate p/T when a period T is defined; pure mean transfer rate k and speed u=kd, where d is the charge transfer distance. The inverse decay length β for the exponential fit k=k0exp(-βd) and the exponent η for the power-law fit k=k0′N-η are computed. β≈0.2-2 Å-1, k0 is usually 10-2-10-1 PHz, generally ≈10-4-10 PHz. η≈1.7-17, k0′ is usually 10-2-10-1 PHz, generally ≈10-4-10 3 PHz. The results are compared with theoretical and experimental works. This method allows to assess the extent at which a specific DNA segment can serve for charge transfer.